All Unhappy Childhoods Are Unhappy in Their Own Way—Differential Impact of Dimensions of Adverse Childhood Experiences on Adult Mental Health and Health Behavior - Westermair, Anna L.; Stoll, Anne M.; Greggersen, Wiebke; Kahl, Kai G.; Hüppe, Michael; Schweiger, Ulrich (Frontiers in Psychiatry, 2018)
Adverse childhood experiences have consistently been linked with poor mental and somatic health in adulthood. However, due to methodological restraints of the main lines of research using cumulative or selective models, little is known about the differential impact of different dimensions of adverse childhood experiences. Therefore, we gathered data from 396 psychiatric in-patients on the Adverse Childhood Experiences questionnaire, extracted dimensions using factor analysis and compared this dimensional model of adverse childhood experiences to cumulative and selective models. Household Dysfunction (violence against the mother, parental divorce, substance abuse or incarceration of a household member) was associated with poor health behaviors (smoking, alcohol dependency and obesity as proxy marker for an imbalance between energy intake and physical activity) and with poorer socio-economic achievement (lower education and income) in adulthood. The previously re-ported associations of maltreatment and sexual abuse with these outcome criteria could not be cor-roborated and might be due to a type II error due to lack of statistical control for the adverse child-hood experiences that form the Household Dysfunction dimension in our study. Both Maltreatment (emotional and physical neglect and abuse) and Sexual Abuse predicted BPD, PTSD and suicidal behavior. However, the two ACE dimensions showed sufficiently divergent validity to warrant sepa-rate consideration in future studies: Maltreatment was associated with affective and anxiety disorders such as social phobia, panic disorder and major depressive disorder, whereas Sexual Abuse was asso-ciated with dysregulation of bodily sensations such as pain intensity and hunger/satiation. Also, we found both quantitative and qualitative evidence for the superiority of the dimensional approach to exploring the consequences of adverse childhood experiences in comparison to the cumulative and selective approaches.